M. LERMONTOV’S NOVEL “A HERO OF OUR TIME” IN NEW INTERPRETATION: NUANCES OF REALISTIC METHOD - Luiza K. Oliander (Alfred Nobel University Journal of Philology, 2019)
The article deals with the hypothetical view of O. Bogdanova on the evolution of conception in Lermontov’s novel “Geroy nashego vremeni” (“A Hero of Our Time”), taken in the context of modern Lermontov study as a link in further clarification of some aspects of realism development in Russian literature of the 19th-century: from A. Pushkin through M. Lermontov to L. Tolstoy and F. Dostoevsky. It is pointed out that O. Bogdanova, as an adherent of the St. Petersburg Philological School, enters into the dialogical field of Lermontov study, created by many publications: “Venok Lermontovu” (“Wreath to Lermontov”) (1914), “Bibliografiya literatury o M.Yu. Lermontove (1917–1977)” (“Bibliography of Literature about M.Yu. Lermontov (1917– 1977)”) (1980), “Lermontovskaya entsiklopediya” (“Lermontov Encyclopedia”) (1981), “Mikhail Lermontov: pro et contra” (2002), “M.Yu. Lermontov: pro et contra: antologiya” (“M.Yu. Lermontov: pro et contra: anthology”) (2014) et al., as well as doctoral dissertations by V. Lipich, S. Savinkova, L. Zharavina and others. It is emphasized that O. Bogdanova’s analytical re-reading (by Chicherin type) is performed, as V. Markovich said, by the elements of «sophistication and stylistic microanalysis» of the novel “Geroy nashego vremeni” (“A Hero of Our Time”) versions. It is proved that the researcher, focusing on the words century and time, is developing her idea of changing Lermonov’s original conception – to show the hero of 1812–1825. Attention is focused on two Pechorins and on the creative “dialogue” between Lermontov and Pushkin. It is emphasized that O. Bogdanova, with full justification, highlighted as a secondary (“fictitious”) narrator – Kazbich. Bogdanova’s approaches to the mechanism of Lermontov’s polydetermination are analyzed, indirect ways of demonstrating the transforming a hero of the 19th century, like Pechorin was before arriving in the Caucasus and initially in the Caucasus, into a hero of the time — partly in the novel “Bela”, mainly in “Fatalist” and finally in the novel “Mary”. It is noted that the hero’s life is considered both horizontally, taken in the historical atmosphere of the post-Decembrist time, and vertically, leading to our time, including the ontological aspect. The senseforming role of Bogdanova’s discourse is revealed.